Pelatihan Kewirausahaan Menggunakan Modul Gender Entrepreneurship Together (GET) Ahead Bagi Pemuda/I Usia Produktif Di Kota Jayapura - Agustinus Salle; Cornelia Desiana Matani (UNIVERSITAS CENDERAWASIH, 2021)
In an effort to improve the community's economy, raising the spirit of entrepreneurship is an important thing that can be done by the campus. This service activity aims to train the community, especially young people of productive age in getting business ideas, identifying and calculating production costs and doing bookkeeping for recording business transactions and marketing products and services. The training held on 15 and 17 April 2021 at the GARAP Kotaraja Co-Working Space training room, Jayapura City. The participants of the activity were 19 youths aged 19 – 22 years. The training was carried out by introducing the basic concept of gender in business and the equal role of women and men in running their businesses. Participants were then asked to brainstorm ideas about the types of businesses around them and identify applicable business ideas. Furthermore, this training trains participants to calculate the business costs of products and services and then collect these costs into production costs. The following material is about bookkeeping in running a business which is needed to know the financial condition of the business and as a basis for evaluating the condition of the business. The aspect of the ability to do marketing is learned in this training through case study analysis. The mechanism for monitoring and evaluating training activities is carried out through the distribution of pre and post test questionnaires which are distributed to training participants before and after the activity.